3D Parallel Monte Carlo Simulation of GaAs MESFETs - Pennathur, S.; Sandalci, Can K.; Koç, Çetin K.; Goodnick, S. M. (VLSI design (Yverdon, Switzerland), 1998)
We have investigated three‐dimensional (3D) effects in sub‐micron GaAs MESFETs using a parallel Monte Carlo device simulator, PMC‐3D [1]. The parallel algorithm couples a standard Monte Carlo particle simulator for the Boltzmann equation with a 3D Poisson solver using spatial decomposition of the device domain onto separate processors. The scaling properties of the small signal parameters have been simulated for both the gate width in the third dimension as well as the gate length. For realistic 3D device structures, we find that the main performance bottleneck is the Poisson solver rather than the Monte Carlo particle simulator for the parallel successive overrelaxation (SOR) scheme employed in [1]. A parallel multigrid algorithm is reported and compared to the previous SOR implementation, where considerable speedup is obtained.